2016
DOI: 10.1016/j.desal.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Tuning electrodialytic transport properties of heterogeneous cation exchange membrane by the addition of charged microspheres

Abstract: In this study, the sulfonated polystyrene microspheres (MPs) which embraced much 9 smaller particle size and narrower size distribution than those of conventional resin powders (RPs) 10 were synthesized and employed as ion-exchangers exclusively or additives to prepare 11 heterogeneous cation exchange membrane (CEM). Thereupon the effects of the incorporation of 12 the charged MPs on the properties of heterogeneous CEM were investigated. Firstly, the 13 morphologies of the synthesized MPs and the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Figure b showed that the CEM-X exhibited area resistance less than 3 Ω·cm 2 , which was much lower than commercial CAM (6.96 Ω·cm 2 ). Figure c compared the area resistance of membrane CEM-60 with other CEMs reported in the literature. ,, It can be concluded that membrane CEM-60 exhibited comparable area resistance to homogeneous membranes. There were three reasons that may explain the extremely low area resistance.…”
Section: Results and Discussionmentioning
confidence: 91%
“…Figure b showed that the CEM-X exhibited area resistance less than 3 Ω·cm 2 , which was much lower than commercial CAM (6.96 Ω·cm 2 ). Figure c compared the area resistance of membrane CEM-60 with other CEMs reported in the literature. ,, It can be concluded that membrane CEM-60 exhibited comparable area resistance to homogeneous membranes. There were three reasons that may explain the extremely low area resistance.…”
Section: Results and Discussionmentioning
confidence: 91%
“…Conventional membrane resistance analysis is based on AC techniques such as EIS [ 40 , 77 , 78 ] or LCR [ 79 ]. AC resistance is more than its DC resistance owing to the skin effect , i.e., the non-uniform distribution of an AC flowing through a conductor and its tendency to concentrate near the surface of the conductor at a certain level or skin depth (the current density is ca.…”
Section: Resultsmentioning
confidence: 99%
“… r (Ω.cm) σ (S/cm) Type Method Ref. QPECH AEM (QP/A-06) 6.411 0.157 DC Four Probe Co-linear DC Method a Present work PECH-C 6.165 ± 0.185 0.157–0.167 AC Kroll's Method [ 44 ] AM-PP 1.14 ± 0.05 0.88 ± 0.04 DC Kroll's Method [ 44 ] AMX 2.35 ± 0.05 0.425 ± 0.005 AC Kroll's Method [ 78 ] 2.67 0.524 AC EIS DSV 3.07 ± 0.20 0.3255 ± 0.0196 AC Kroll's Method ACS 4.39 ± 0.10 0.225 ± 0.05 AC Kroll's Method Brexar 70 17.54 0.057 AC EIS [ 73 ] Nafion® 115 7.41 ± 0.92 0.137 ± 0.17 AC EIS AMPS (58)-GDMA (42) 0.77 ± 0.07 0.0132 ± 0.00...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…with the concentration ratio. 56 The plots of V Diff vs. ln(C 1 /C 2 ) for various TPU-PSS/DVB membranes are shown in Fig. 7.…”
Section: Membrane Potential Measurementmentioning
confidence: 99%